Pertumbuhan Perusahaan dan Struktur Modal terhadap Nilai Perusahaan pada Sub Sektor Makanan dan Minuman di Bursa Efek Indonesia - Nurhayati Olii; Eka Zahra Solikahan; Ariawan Ariawan (Journal of Technopreneurship on Economics and Business Review, 2021)
Increasing the prosperity of the owners or shareholders through increasing the firm value is the main goal of the corporation. Therefore, it is necessary to make efforts to grow the company and use an optimal capital structure in accordance with the trade-off theory that predicts a positive relationship to the value of the company. This study aims to determine the effect of company growth and capital structure on increasing company value. The research method uses a quantitative approach, using the purposive sampling technique in the food and beverage sub-sector, and multiple regression is used for data analysis. The finding of the study indicates that firm growth has a negative and insignificant effect on firm value. Capital structure has a negative and insignificant effect on firm value. Together, firm growth and capital structure have no significant effect on firm value in the food and beverage sub-sector. The growth of a firm requires large investment costs and optimizing the funding of the company’s capital structure.